PELATIHAN DISEMINASI PENDIDIKAN KARAKTER ANTI KORUPSI BAGI PENGURUS OSIS SMP NEGERI 31 PADANG - Dewi Anggraini; Tengku Rika Valentine; Zulfadli Zulfadli (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Corruption is an extraordinary crime (extraordinary crime), so the handling must be done with extraordinary efforts. In this reform era, corruption is increasingly rampant involving various actors, from the central government to the lowest. From Transparency International (TI) data, Indonesia's 2017 Corruption Perception Index (CPI) is 37 and is ranked 96 out of 180 countries surveyed globally. Responding to the increasingly prevalent phenomenon of corruption, the world of education has begun to improve to answer the challenges of the swift currents of corruption. One of the efforts made is curriculum change. Curriculum changes that have been intensively discussed lately are the inclusion of anti-corruption character education at the pre-school to tertiary education levels. The purpose of this activity is to provide OSIS administrators with an understanding of anti-corruption character education, including understanding, rules, and implementation of anti-corruption character education in junior high schools. In contrast, the methods used are lectures, question and answer methods, and simulations with film screenings about anti-corruption characters in schools. The results of this activity showed that of the 30 (thirty) OSIS administrators who attended this event, almost 99% of them knew that corruption was a violation of the law. They could also explain corrupt practices that occurred in the school environment and their family environment, and sometimes they also become the perpetrator of the action.